2016
DOI: 10.1016/j.micres.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of multidrug resistant Listeria monocytogenes by peptides isolated from combinatorial phage display libraries

Abstract: The aim of the study was to isolate and characterize novel antimicrobial peptides from peptide phage library with antimicrobial activity against multidrug resistant Listeria monocytogenes. Combinatorial phage-display library was used to affinity select peptides binding to the cell surface of multidrug resistant L. monocytogenes. After several rounds of affinity selection followed by sequencing, three peptides were revealed as the most promising candidates. Peptide L2 exhibited features common to antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For instance, a phage display approach was used to identify peptides capable of binding to the cell surface of E. coli resulting in a novel antibacterial peptide sequence with activity against both E. coli and P. aeruginosa , although the resultant peptide was unfortunately only moderately active and did not inhibit other tested bacteria (Rao et al, 2013). A similar strategy was employed to identify AMPs with selective activity against Listeria monocytogenes (Flachbartova et al, 2016). Furthermore, phage display has successfully identified peptides with antiviral (Ojeda et al, 2016) and antifungal activity (de Oliveira et al, 2016) demonstrating the utility of such a technique to explore other activity landscapes within the chemical space of HDPs.…”
Section: Activity Landscapes Of Host Defense Peptidesmentioning
confidence: 99%
“…For instance, a phage display approach was used to identify peptides capable of binding to the cell surface of E. coli resulting in a novel antibacterial peptide sequence with activity against both E. coli and P. aeruginosa , although the resultant peptide was unfortunately only moderately active and did not inhibit other tested bacteria (Rao et al, 2013). A similar strategy was employed to identify AMPs with selective activity against Listeria monocytogenes (Flachbartova et al, 2016). Furthermore, phage display has successfully identified peptides with antiviral (Ojeda et al, 2016) and antifungal activity (de Oliveira et al, 2016) demonstrating the utility of such a technique to explore other activity landscapes within the chemical space of HDPs.…”
Section: Activity Landscapes Of Host Defense Peptidesmentioning
confidence: 99%
“…Then, phages that did not bind efficiently to the target are washed, while strongly phage-binding targets are eluted by different methods. The phage display technique has been used to find peptides able to detect enzymes, whole eukaryotic and prokaryotic cells, including MDR strains, and assess if they presented microbicidal activities [266][267][268][269]. In addition, it has been observed that foreign peptides can be modified in their conformation on the phage surfaces and resistance to chemical-physical environment compared to the wild-type [270,271].…”
Section: Phage Engineeringmentioning
confidence: 99%
“…Listeriosis is highly lethal and has been associated with foodborne epidemics over the past decade [ 64 ]. Z. Flachbartova et al used the phage-display random-peptide library Ph.D.-12 to target MDR L. monocytogenes [ 23 ]. The selected peptides (L2 and L3) showed antibacterial activities against L. monocytogenes , and their MIC values were both 30 µM.…”
Section: Application Of Phage Display In the Antibacterial Fieldmentioning
confidence: 99%